Risk Factors for the Incidence of Cholelithiasis at Ibnu Sina Makassar Hospital for the 2021-2023 Period - Yusuf, Awalia Rezeki S; Bamahry, Aryanti R; Yanti, Andi Kartini Eka; Gani, Aziz Beru; Kanang, Indah Lestari Daeng (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Cholelithiasis is an important health problem with severity and septic complications related to the type of gallstone. Several risk factors also influence the incidence of cholelithiasis. Objective: This study aims to determine the distribution of cholelithiasis patients based on gender, Body Mass Index (BMI), age, childbearing age in women, triglyceride levels, and total cholesterol levels at Ibnu Sina Hospital Makassar in the period 2021 to 2023. Method: This type of research is descriptive using a Cross Sectional Study approach, namely explaining the risk factors for the incidence of cholelithiasis at Ibnu Sina Hospital Makassar. Results: The distribution of cholelithiasis patients at Ibnu Sina Hospital Makassar in 2021-2023 shows that the risk factors are mostly female, overweight/obesity, age >40 years, hypertriglyceridemia, and hypercholesterolemia. However, women of childbearing age suffer less from cholelithiasis than older women. Conclusion: Cholelithiasis at Ibnu Sina Hospital Makassar in 2021-2023 is more common in women, >40 years of age, overweight/obesity, hypertriglyceridemia, and hypercholesterolemia, with a lower incidence in women of childbearing age compared to old age.